Antarctic explorers at Hector Airport, Fargo, N.D. - Anderson, David, 1883-1962 (North Dakota State University Libraries, Institute for Regional Studies, 1933)
Bernt Balchen, Lincoln Ellsworth and Sir Hubert Wilkins standing in front of airplane, dressed in cold weather clothing. Another man is seated in the cockpit. Gelatin silver prints; 13 x 18 cm. Title supplied by staff.